Two Theileria parva CD8 T Cell Antigen genes are more variable in buffalo than cattle parasites, but differ in pattern of sequence diversity - Pelle, Roger; Graham, S.P.; Njahira, Moses N.; Osaso, J.; Saya, Rosemary M.; Odongo, David O.; Toye, Philip G.; Spooner, P.R.; Musoke, A.J.; Mwangi, David Miano; Taracha, E.L.N.; Morrison, W. Ivan; et al. (Public Library of Science, 2011)
Theileria parva causes an acute fatal disease in cattle, but infections are asymptomatic in the African buffalo (Syncerus caffer). Cattle can be immunized against the parasite by infection and treatment, but immunity is partially strain specific. Available data indicate that CD8+ T lymphocyte responses mediate protection and, recently, several parasite antigens recognised by CD8+ T cells have been identified. This study set out to determine the nature and extent of polymorphism in two of these antigens, Tp1 and Tp2, which contain defined CD8+ T-cell epitopes, and to analyse the sequences for evidence of selection.